2022
DOI: 10.21037/atm-22-2543
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms in drug metabolism genes predict the risk of refractory myasthenia gravis

Abstract: Background: Nearly 10% to 20% of myasthenia gravis (MG) patients are refractory to conventional treatment for unclear reasons. The study aimed to explore the relationship between drug metabolism gene polymorphisms and refractory MG.Methods: One hundred and thirty-one MG patients (33 in the refractory group; 98 in the non-refractory group) admitted to Tongji Hospital were included in this retrospective study. Improved multiplex ligation detection reaction (iMLDR) was used to genotype 13 polymorphisms (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 39 publications
(48 reference statements)
0
1
0
Order By: Relevance
“…One study found that certain single nucleotide polymorphisms (SNPs) in the glucocorticoid gene influence steroid response in patients with MG (46). Similarly, another study identified polymorphisms in cytochrome P450 3A5 (CYP3A5) and heat shock protein 90AA1 (HSP90AA1) associated with refractory versus non-refractory MG (47). Rose et al demonstrated that AChR antibodies have varied specificity for epitopes on the acetylcholine receptor.…”
Section: Discussionmentioning
confidence: 99%
“…One study found that certain single nucleotide polymorphisms (SNPs) in the glucocorticoid gene influence steroid response in patients with MG (46). Similarly, another study identified polymorphisms in cytochrome P450 3A5 (CYP3A5) and heat shock protein 90AA1 (HSP90AA1) associated with refractory versus non-refractory MG (47). Rose et al demonstrated that AChR antibodies have varied specificity for epitopes on the acetylcholine receptor.…”
Section: Discussionmentioning
confidence: 99%